Small-scale screening procedure to identify deflagration potential of bulk solids - Christian Aeby; Delphine Berset; Thomas Gmeinwieser; Luisa Heinz; Pascale Hoehn; Roland Obermüller; Gerhard Schoppel; Mischa Schwaninger (Chemical Engineering Transactions, 2022)
A novel screening method is presented for the assessment of the deflagration potential of bulk solids. It is based on a combination of closed and open thermal stability measurement. The closed measurement is performed as Closed Pressure Vessel Test, which is already proven in use regarding explosives screening. The open measurement is performed as "Lütolf Quick Test for the Determination of Exothermic Decomposition". With the proposed test combination, the sample amount is significantly reduced to a minimum of 4 g. Based on numerous deflagrator samples, as well as of partly and fully de-sensitized deflagrators, mixed with inert Diatomaceous earth, the successful application of this test combination is demonstrated.